What I Learned about Churches of Christ and Christian Churches/Churches of Christ - Williams, David N. (Stone-Campbell journal, 2012)
Churches of Christ (a cappella) and Christian Churches/Churches of Christ (independent) both contain multiple streams. In the early twentieth century there were three streams in the Churches of Christ. Today there are two. There are currently three streams in the Christian Churches/Churches of Christ. Similarities linking streams across these two groups and with the leadership of the Christian Church (Disciples of Christ) are rooted in similar views of the norm of the restoration of apostolic Christianity.